2020
DOI: 10.18510/hssr.2020.8170
|View full text |Cite
|
Sign up to set email alerts
|

Tax Compliance With Taxpayer Awareness as an Intervening Variable

Abstract: Purpose of the study: This research explores the role of taxpayer awareness as an intervening variable in analyzing the effect of tax penalties and tax audits on taxpayer compliance. Methodology: The Research to use a purposive sampling method with the type of sample selection based on consideration the judgment sampling. Main Findings: The results of the SmartPLS Version 3.0 test provide evidence that tax penalties and tax audits carried out by professional auditors proved to be able to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
2
8
0
4
Order By: Relevance
“…According to research (Cahyanti, Wafirotin, & Hartono, 2019) simultaneously testing that there is an effect of tax awareness and morale on taxpayer compliance. Furthermore, in the research of Idrus et al (2020) prove the existence of tax awareness that has an impact on taxpayer compliance. From previous research, it can be concluded that there is an influence of the dependent variable with the independent variable.…”
Section: The Effect Of Tax Morals On Taxpayer Compliance Through Tax Awarenessmentioning
confidence: 93%
See 4 more Smart Citations
“…According to research (Cahyanti, Wafirotin, & Hartono, 2019) simultaneously testing that there is an effect of tax awareness and morale on taxpayer compliance. Furthermore, in the research of Idrus et al (2020) prove the existence of tax awareness that has an impact on taxpayer compliance. From previous research, it can be concluded that there is an influence of the dependent variable with the independent variable.…”
Section: The Effect Of Tax Morals On Taxpayer Compliance Through Tax Awarenessmentioning
confidence: 93%
“…In Lisa and Hermanto (2018) shows that taxpayer awareness has a significant effect on taxpayer compliance. Furthermore, in the research of Idrus et al (2020) prove the existence of tax awareness that has an impact on taxpayer compliance. However, there have been no previous researchers who have tested the effect of nationalism on taxpayer compliance through tax awareness, and the effect of tax morale on taxpayer compliance through tax awareness.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations